2021
DOI: 10.1038/s41598-021-87546-8
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Carvacrol and PPARγ agonist, pioglitazone, affects inhaled paraquat-induced lung injury in rats

Abstract: Exposed rats to normal saline and paraquat (PQ) aerosol as control and PQ group, rats exposed to PQ and treated with 20 and 80 mg/kg/day carvacrol, 5 and 10 mg/kg/day pioglitazone, low dose of pioglitazone + carvacrol and 0.03 mg/kg/day dexamethasone (Dexa) for 16 days after the end of PQ exposure were studied (n = 6 in each group). Lung pathological changes, tracheal responsiveness to methacholine and ovalbumin (OVA) as well as transforming growth factor beta (TGF-β) and interleukin (IL)-6 level in the lung t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…This study was designed to evaluate the effects of simvastatin‐loaded in PLGA nanoparticles (PLGA‐SV NP) on pulmonary fibrosis induced by administration of inhaled PQ along with the possible mechanisms of these effects. The inhaled PQ dose (54 mg/m 3 ) and the duration of the study was selected based on previous published studies 26,30 . In our study, inhalation of PQ aerosol (54 mg/m 3 ) induced systemic inflammation and lung injury which confirmed with body weight loss, increased tracheal responsiveness to methacholine, lung histology changes, as well as elevated TNF‐α and IL‐6 levels in the serum are supported by several previous studies.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This study was designed to evaluate the effects of simvastatin‐loaded in PLGA nanoparticles (PLGA‐SV NP) on pulmonary fibrosis induced by administration of inhaled PQ along with the possible mechanisms of these effects. The inhaled PQ dose (54 mg/m 3 ) and the duration of the study was selected based on previous published studies 26,30 . In our study, inhalation of PQ aerosol (54 mg/m 3 ) induced systemic inflammation and lung injury which confirmed with body weight loss, increased tracheal responsiveness to methacholine, lung histology changes, as well as elevated TNF‐α and IL‐6 levels in the serum are supported by several previous studies.…”
Section: Discussionsupporting
confidence: 78%
“…The rats were exposed to saline solution in the control group or different treatments of PQ in the other groups eight times, each time for 30 min, every other day, for 15 days. The route of exposure was inhalation through nebulizer (Omron CX3, Japan, particle size 3–5 μm) with air flow of 8 L/min and delivered to animals' head box with dimensions of 15 × 18 × 30 cm 26 . Animals were treated with SV (20 mg/kg, BW/day) or PLGA‐SV (5, 10 and 20 mg/kg, BW/day) via inhalation 30 min after the end of the PQ exposure period.…”
Section: Methodsmentioning
confidence: 99%
“…In a model of inhaled paraquat (PQ)‐induced lung injury, the effects of carvacrol (20 and 80 mg/kg/day, for 16 days), pioglitazone (5 and 10 mg/kg/day), pioglitazone + carvacrol combination, and 0.03 mg /kg/day dexamethasone were examined for 16 days after the end of paraquat exposure. The results demonstrated that lung pathological changes, TR to methacholine and OVA, TGF‐β, and IL‐6 level in the lung tissue homogenize as well as oxidant and antioxidant levels were increased in paraquat group which significantly ameliorated by carvacrol and pioglitazone dose‐dependently as well as the combination of carvacrol + pioglitazone similar to the effect of dexamethasone (Amin, Memarzia, Rad, Kazerani, & Boskabady, 2021).…”
Section: Resultsmentioning
confidence: 88%
“…The effects of Z. multiflora extract and pioglitazone on cytokine levels in PQ-exposed rats were supported by the above studies. The protective effect of carvacrol, one of the main constituents of this plant on lung inflammation induced by inhaled PQ, was also reported [ 45 ].…”
Section: Discussionmentioning
confidence: 96%